2023
DOI: 10.1111/ele.14234
|View full text |Cite
|
Sign up to set email alerts
|

Recent exposure to environmental stochasticity does not determine the demographic resilience of natural populations

Abstract: Ongoing global shifts in the timing and magnitude of environmental variation warrant an understanding of the processes underlying the capacity for populations to resist and recover from disturbances (Angeler & Allen, 2016; Standish et al., 2014) (i.e. their resilience;Holling, 1973). However, half a century since Holling first defined resilience in ecological systems (Holling, 1973), we still do not know whether and how past environmental regimes shape the resilience of extant species (Walker, 2020).Resolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 102 publications
1
7
2
Order By: Relevance
“…In P. clavata populations exposed and unexposed to MHWs, the main differences in resistance came from progression and stasis. These results contrast, to some extent, with previous studies suggesting that both reproductive and survival demographic processes are important drivers of demographic resistance (Cant et al, 2023; Capdevila, Stott, et al, 2022). Cant et al (2023) observed that greater investment in survival reduces population resistance (they measured first step attenuation instead of its inverse, as done here), while greater reproductive investment increases resistance potential.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In P. clavata populations exposed and unexposed to MHWs, the main differences in resistance came from progression and stasis. These results contrast, to some extent, with previous studies suggesting that both reproductive and survival demographic processes are important drivers of demographic resistance (Cant et al, 2023; Capdevila, Stott, et al, 2022). Cant et al (2023) observed that greater investment in survival reduces population resistance (they measured first step attenuation instead of its inverse, as done here), while greater reproductive investment increases resistance potential.…”
Section: Discussioncontrasting
confidence: 99%
“…Demographic resilience is tightly linked to the life history of species (Cant et al, 2023; Capdevila, Stott, et al, 2022; Field et al, 2019). For instance, species with slow life history strategies (high investment in survival, low reproduction, and slow growth) often require longer times to recover (Cant et al, 2023; Capdevila, Stott, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analyses often rely on the collation of published data to obtain sufficient sample sizes. There are numerous recent examples of this (Dalgleish et al 2010, Bullock et al 2012, Burns et al 2013, and large-scale collaborative efforts to collate global demographic and life history and related data are increasingly common (Wright et al 2004, Loh et al 2005, Kattge et al 2011, Salguero-Gómez et al 2015, Capdevila et al 2022, Hernández-Yáñez et al 2022, Cant et al 2023. Such databases provide a rich resource for workers focussing on life-history strategies and demographic performance.…”
Section: Introductionmentioning
confidence: 99%
“…matrix population models, population modelling, propagation, simulation, uncertainty such as COMPADRE (Salguero-Gómez et al, 2015) and COMADRE (Salguero-Gómez et al, 2016), have greatly contributed to the field of predictive ecological modelling by providing access to thousands of published MPMs and metadata for comparative analyses (Cant et al, 2023;Enríquez et al, 2022;Hernández-Yáñez et al, 2022;Lanuza et al, 2023). However, these repositories do not provide any uncertainty metrics for the underlying parameters of the matrices they hold or their derived quantities, causing uncertainty omission.…”
Section: Introductionmentioning
confidence: 99%